Internet-delivered, preoperative, preparation program (I-PPP): the effect of the timing of delivery on anxiety in children undergoing day surgery procedures. Issue 3 (2nd July 2020) - Wright, Kristi D.; Kim, Jinsoo; Ratcliffe, Chelsy R. D.; Sharpe, Donald; Wilson, Stuart; O'Brien, Jennifer; Raazi, Mateen
ABSTRACT: Research has demonstrated the effectiveness and efficacy of the Internet-delivered, preoperative program (I-PPP) in alleviating child anxiety when the I-PPP is completed prior to the day of surgery. However, recent evidence has suggested that preparation on the day of surgery may be an effective option. The objective of this investigation was to explore the effect of the timing of the delivery of the I-PPP (i.e., prior to day of surgery versus day of surgery) on anxiety in children 3-10 years of age undergoing a day surgery procedure. Eighty children undergoing day surgery procedures at a local hospital and their parents/guardians participated. Primary outcome measures were (a) observer-rated child anxiety, (b) induction compliance. For observer-rated child anxiety, results demonstrated a main effect for time of assessment, F (2, 150) = 16.64, p = .001, η p 2 = .18. No group differences were observed nor group by time of assessment interaction. No group differences were observed for induction compliance. Our findings demonstrated that the timing of the delivery of the I-PPP does not influence the experience of child anxiety. However, the I-PPP delivered prior to the day of surgery may be more preferable for families and the intervention setting.